Implementasi Standar Operasional Prosedur Penggeledahan Sebagai Upaya Pencegahan Masuknya Barang Terlarang Di Rutan Kelas I Surabaya - Vera Rimbawani Sushanty; Dibyo Triwidodo, Moch (Jurnal Hukum Ekualitas, 2025)
Correctional Institutions, hereinafter referred to as LAPAS and State Detention Centers, hereinafter referred to as RUTAN, are places to carry out coaching for prisoners and correctional students. Related to the ease with which prohibited items enter Correctional Institutions and Detention Centers. It is necessary to think about the lack of enforcement of performance rules. Particularly in terms of searching convicts, detainees, visitors and officers themselves to prevent the entry of prohibited items. Search activities that are intended to prevent the entry of prohibited items must pay attention to the excellent service system for visitors, officers and detainees. The prime service system can be realized if there is a Standard Operating Procedure (SOP) as a benchmark in the framework of transparency. This research focuses on the problems and obstacles in the implementation of Standard Operating Procedures (SOP) Searches in preventing the entry of prohibited items into Class I Detention Centers in Surabaya. This research is an empirical legal research using two data collection methods, namely documentation and interviews. The results of the study showed that there were still obstacles in the implementation of SOP searches to prevent the entry of prohibited items caused by the overcapacity of the Class I Detention Center in Surabaya which had an impact on the large number of visitors and luggage that was not proportional to the number of officers.